Section 19a GWB as a measure of counter-power against "Undertakings with Paramount Significance for Competition across Markets" - Annika Stöhr (Technische Universität Ilmenau, Institut für Volkswirtschaftslehre, 2024)
A central component of the modernization of German abuse control, implemented with the 10th amendment of the German Act Against Restraints of Competition ("Gesetz gegen Wettbewerbsbeschränkungen", GWB), is Section 19a, which has been the subject of considerable discussion both before and after its implementation. The amendment introduces a new criterion for determining market power, namely the designation of undertakings with socalled "paramount significance for competition across markets" (UPSCAM) (Sec. 19a (1) GWB). This is designed to serve as a measure of counter-power and as a means of overcoming the limitations of traditional market power determinations in digital (platform) markets. Moreover, it allows for the implementation of ex-ante measures that prohibit conduct deemed to be particularly anti-competitive (Sec. 19a (2) GWB). This article examines the initial case practice of the German Federal Cartel Office (FCO) with the new instrument and subjects it to an economic analysis. The introduction of Sec. 19a GWB has provided a further intervention option for addressing specific competition issues within digital ecosystems. This enables the competition authority to intervene in a more effective and timely manner when cross-market power is exploited. However, the assessment of the criteria set forth in Sec. 19a (1) GWB has thus far been rather haphazard. This issue should be addressed through further concretization in the context of future case practice and, if necessary, the issuance of corresponding guidelines. The first case practice of Sec. 19a (2) GWB has yielded promising results, including the imposition of commitments and swift alterations in the behavior of the firms in question. Furthermore, the possibility of incorporating these Sec. 19a GWB proceedings into ongoing ones highlights the distinctive role of Sec. 19a GWB as a genuinely novel instrument within the domain of antitrust law. However, it is essential to acknowledge that the absence of enforcement and sanctioning mechanisms in the event that no commitments are reached by the firms may present a potential limitation.
Keywords: 330